Distribution of articles in Malaysian secondary school English language textbooks - Mukundan, Jayakaran; Leong, Amelia Chiew Har; Nimehchisalem, Vahid (Canadian Center of Science and Education, 2012)
This paper reports the results of a corpus-based study on English grammar articles presented in the Malaysian Form 1 to Form 5 English Language textbooks. The study aimed to find out the distribution patterns of the articles and the distributions of their colligation patterns in the secondary school English Language textbooks. The findings showed that all the three articles (a, an, the) are presented in all the five English Language textbooks and that their frequency of occurrences has an increasing trend from Form 1 to Form 5. However, the distributions of the colligation patterns of the articles showed inconsistency from one form to another. Some colligation patterns were over-emphasized while others were neglected in the English language textbooks. This study indicates that a textbook corpus can be useful in analyzing the presentation of grammatical structures (articles, in the case of this research). The findings can provide guidance to teachers to improve their pedagogical practices in the teaching of articles and to cater to the weaknesses of the presentation of articles in the textbooks.